Household food insecurity and nutritional status among adolescents in Kuantan, Pahang - Yahya, Noor Atirah; Mohd Abu Bakar, Wan Azdie; Sidek, Suriati; Ab Ghalib, Halimatun Saadiah; Mat Ya, Roselawati; Abdul Rahman, Rozlin (2018)
The link between food insecurity and nutritional status has been studied comprehensively, but the results were mixed depending on the data source and subpopulation involved. The objective of this study is to investigate the prevalence of household food insecurity and nutritional status among secondary school children in Kuantan, Pahang. Data were obtained from 530 students from 12 secondary schools in five different sub-districts in Kuantan, Pahang. Food security parameters were measured using validated Radimer/ Cornell Hunger and Food Security Instrument (Malay version). The weight and height were measured and height for age and BMI for age were calculated using WHO Anthroplus® software. 76.4% of the students were living in food insecurity while the other 23.6% were food secure. From food insecurity category, 31.5% of them were sub-categorized into household food insecure, 7.5% of them were experiencing food insecurity in individual level (mother or father) and 37.5% of them were in child hunger category. Out of 5 subdistricts, Ulu Kuantan had the highest food insecure to food secure households’ ratio (5:1) compared to other sub-districts. According to WHO cut-off point, 16.6% and 14.2% of the subjects were overweight and obese respectively, 9.3% of them fell into underweight category and others were normal. 26.5% of the underweight students were severely wasted and 47.5% of students were stunted. The prevalence of overweight and obese were higher in female subjects and food insecure households (58.7% and 77.3% respectively) compared to male and food secure households (41.7% and 22.7% respectively). This study showed that the food insecurity is present in Malaysian households and the prevalence of overweight and obesity is high among adolescents in Kuantan. More synchronize actions from both government and non-governmental agencies are necessary to overcome these problems.